Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.4103/0256-4947.51488
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of abnormal Pap smears in developing countries : A report from a large referral hospital in Saudi Arabia using the revised 2001 Bethesda System

Abstract: BACKGROUNDReports describing the frequency and pattern of abnormal Pap smears in developing countries using the revised Bethesda system for Pap smear are few. We studied the pattern of cervical intraepithelial lesions and carcinoma detected in Pap smears of Saudi females in the western region of Saudi Arabia using the revised system.METHODSAll cervical Pap smears reported in the Department of Pathology of King Abdulaziz Medical City, Jeddah, from 1 January 1998 to 31 August 2005 were reclassified according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 6 publications
(8 reference statements)
3
14
2
Order By: Relevance
“…[89] Two studies showed similar prevalence to our current findings. [1011] The mean age of the cases diagnosed as SCC was 35.8 years. The average age of SCC in all the Saudi studies was nearly similar.…”
Section: Discussionmentioning
confidence: 99%
“…[89] Two studies showed similar prevalence to our current findings. [1011] The mean age of the cases diagnosed as SCC was 35.8 years. The average age of SCC in all the Saudi studies was nearly similar.…”
Section: Discussionmentioning
confidence: 99%
“…Studies profiling Pap smears examined at University Hospitals have revealed precursor lesions of cervical cancer (14, 1820). A study combining HPV detection with Pap test in 100 women undergoing voluntarily cervical cytological screening have found 6% HPV-positive cases that consisted of 5% high-risk and 1% low risk HPV (21).…”
Section: Hpv Infection and Related Cancersmentioning
confidence: 99%
“…Most of the published data about cervical changes among women in Saudi Arabia did not investigate the existence of HPV [9][10][11][12]. Aside from a few studies [13][14][15][16], there is insufficient information about HPV prevalence and its involvement in cervical cancer in Saudi Arabia, especially from population-based studies.…”
Section: Introductionmentioning
confidence: 95%
“…The majority of these genotypes are harmless. However, some are classified as low risk, causing genital warts (HPV- 6,11,40,42,43,44,53,54,61,72,73, and 81), while others were considered high risk (HPV- 16,18,31,33,35,39,45,51, 52, 56, 58, 59, and 68) for cervical cancer [3,4]. HPV-16 and HPV-18 are globally believed to be directly involved in the cervical carcinogenesis process [5][6][7].…”
Section: Introductionmentioning
confidence: 99%